The rs1477196 SNP of the FTO Gene is Associated with Primary Knee Osteoarthritis in a Female Population from Northern Mexico - Rubén D. Arellano-; Faviel F. González-Galarza; Denisse Prone-Olazábal; Daniel O. Arellano-Ramírez; Diego F. Arellano-Ramírez; Cristina S. Argüello-Beltrán; Michelle A. Tovar-Aguilar; Mónica Berúmen-Rodríguez; Adria I. Prieto-Hinojosa; Alejandra Méndez-Hernández; Rafael Argüello-Astorga (Permanyer, 2024)
Background: Osteoarthritis is a frequent rheumatic disease. Some single-nucleotide polymorphisms of the gene associated with fat mass and obesity are associated with increased body mass index and knee osteoarthritis. Objective: The objective of this study was to analyze the association of single nucleotide polymorphism rs1477196 of the fat mass and obesity gene with primary knee osteoarthritis. Methods: This observational and cross-sectional study included 347 Mexican participants. We performed the genotypification analysis with TaqMan® probe C_2031262_10 for rs1477196 (Thermo Fisher Scientific). Multivariate analysis included covariables such as age, type 2 diabetes, obesity, and postmenopause. Results: Type 2 diabetes, obesity, and postmenopause were associated with primary knee osteoarthritis in female participants. We did not find an association between rs1477196 and obesity. In the codominant and dominant genetic models, rs1477196 was significantly associated with primary knee osteoarthritis only in the female group, including in the model adjusted by other covariables (odds ratio = 2.517; 1.035-6.123; p = 0.042 and odds ratio = 2.387; 1.054-5.407; p = 0.037, respectively). The interaction between rs1477196 and obesity was significantly associated with primary knee osteoarthritis in female participants (p = 0.039 and p = 0.043). Conclusions: Our findings suggest that the rs1477196 variant of the fat and obesity mass gene may be associated with the risk of primary knee osteoarthritis in women.